2006
DOI: 10.1016/j.rapm.2006.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A Subgluteal Approach to the Sciatic Nerve in Adults at 10 cm From the Midline

Abstract: This report shows that a sciatic nerve block can be performed in the subgluteal area at 10 cm from the midline in adult patients of both sexes and various sizes. Anesthesia of the posterior thigh is not consistently accomplished with this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
4
6
0
Order By: Relevance
“…Specifically, after regression analysis, females of the same age, weight, and height have an expected nerve division that is 0.40 cm deeper than males. Adipose tissue appears to be a more significant regulator than skeletal tissue with regard to skin-nerve depth [9]. This is reflected in our data, where intuitively, greater weight increased skin-nerve depth.…”
Section: Discussionsupporting
confidence: 66%
“…Specifically, after regression analysis, females of the same age, weight, and height have an expected nerve division that is 0.40 cm deeper than males. Adipose tissue appears to be a more significant regulator than skeletal tissue with regard to skin-nerve depth [9]. This is reflected in our data, where intuitively, greater weight increased skin-nerve depth.…”
Section: Discussionsupporting
confidence: 66%
“…This approach includes identifying the popliteal blood vessels in the popliteal crease first, and then locating the sciatic nerve by moving the probe cephalad along the tibial nerve. Our data, obtained in lean, healthy, and relatively young volunteers, suggested that starting about 5 cm distal to the subgluteal fold, possibly 10 cm lateral from the midline (i.e., the intergluteal sulcus) as proposed by Franco et al (9), might be for this population, an alternative useful approach for ultrasonographic identification of the sciatic nerve via a posterior approach. Interestingly, according to the results of this study, the optimal point for the sciatic nerve block would be very close to that recommended by Di Benedetto et al (8).…”
Section: Discussionsupporting
confidence: 55%
“…Mean depths of the sciatic nerve at the subgluteal fold between 4.5 and 8.5 cm found by sciatic nerve stimulation have been reported (8–10). In our volunteers, the ultrasonographically measured mean depth of the sciatic nerve at the subgluteal fold was only 3.2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches to the sciatic nerve are utilized. For femur fractures, more proximal approaches, such as the classic Labat technique or the subgluteal approach [Di Benedetto et al, 2002;Franco et al, 2006], are appropriate. For leg and ankle fractures, a more distal approach, such as a popliteal catheter, may be more suitable, as sparing of the hamstring musculature is important for ambulation.…”
Section: Femur Fracturesmentioning
confidence: 99%